body, technique and play in childhood: notes on the critical theory of theodor w. adorno - Salgado, Mara [UNESP] (State Univ Rio De Janeiro, 2019)
This paper discusses the status of about childhood in Theodor Adorno's critical theory, focusing on his reflections on the body, on technique and on play that mark childhood as another form of reason. Childhood is portrayed by Adorno as a place of the first utopia, that longed for and permanently uninhabited homeland that resists any rescue attempt, but illuminates the desire we once experienced, in a play between body and thought, dream and reality. Adorno's child evokes the experience of another order of reason that feeds on the memory of the human's animal nature, without, however, being exempt from the dominant historical forces that affect the processes of subjectivation. These reflections start with the writings of Adorno and what his dialogues with interlocutors, such as Benjamin, Freud, and Huizinga, contribute to the analysis of the topic. In the second part of the article, in an effort to understand the potential and the limits of technologically-mediated play, we discuss several studies of virtual reality, especially electronic games. Conjectures about how contact with reality is already damaged in childhood by the relationship with technology, which establishes a desire for instant gratification, suggest a critique of the quality of attention that children receive in their education, and provide clues about the increasing appearance of socio-affective disorders, which culminate in the preference to dispense with time, the body, and real contact with other children in favor of electronic play.
Keywords: childhood; body; technique; play; eletronic games; critical theory